Efficacy of endocuff - assisted colonoscopy in the detection of colorectal polyps - Tran, Thi Thuy Tien; Nguyen, Thi Huyen Thuong; Tran, Van Huy (Tạp chí Y Dược Huế, 2024)
Background: Colonoscopy is the gold standard for detecting colorectal adenomas and cancers. However, it fails to visualize the entire colon mucosa and consequently a significant number of polyps are still being missed. Endocuff is a new device that can be attached to the tip of the colonoscope to improve mucosal visualization, hence the quality in colonoscopy. This study aimed to describe the clinical characteristics and endoscopic images of colorectal polyps of patients who were endoscopically detected polyps and to assess the diagnostic yield of Endocuff – assisted colonoscopy (EAC) in comparison with standard colonoscopy (SC). Subjects and methods: An observational study was performed to compare EAC versus SC. A total of 308 adults ≥ 18 years referred for colonoscopy were randomly divided into two groups between 06/2022 and 07/2023, the EAC group included 154 adults and the standard colonoscopy included 154 adults. Results: Compared with standard colonoscopy, the PDR in patients increased by about 11% (70.1% vs. 59.1%, p<0.05) with the use of the Endocuff. The ADR was higher for EAC than for standard colonoscopy (20.8% vs. 16.2%). Polyp, adenoma ≤ 5mm and mean number of detected polyps per procedure increased significantly with the use of the Endocuff. No significant differences between EAC and standard colonoscopy groups in ileal intubation rate, cecal intubation time and withdrawal time. Conclusions: Endocuff-assisted colonoscopy seems to be safe and may bring benefits for improving the polyp/adenoma detection rates and the mean number of adenomas identified per patient, as compared with SC